2017
DOI: 10.1186/s40066-017-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ soil knowledge, fertility management logic and its linkage with scientifically analyzed soil properties in southern Ethiopia

Abstract: Background: Farmers' locally have acquired knowledge from generations of experience and experimentation that fit local conditions. Yet, the scientific approach less used farmers' soil knowledge (FSK) and site-specific soil information. The objectives of this study were to investigate FSK and rationality; to demonstrate how FSK relates to scientifically analyzed soil properties; and to explore the implemented soil management practices and crop performances in selected districts of Wolaita zone, southern Ethiopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Such differences can explain why soil testing did not pick up fertility differences perceived by farmers. The reported mismatch is consistent with Gruver and Weil () but contrary to several similar studies that reported good agreement between farmer and laboratory assessments (Berazneva, McBride, Sheahan, & Guerena, ; Laekemariam, Kibret, & Mamo, ; Yageta, Osbahr, Moromoto, & Clark, ; Yeshaneh, ). The differences in farmer‐identified fertility classes in these studies were largely attributed to soil management rather than inherent properties of the soil.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Such differences can explain why soil testing did not pick up fertility differences perceived by farmers. The reported mismatch is consistent with Gruver and Weil () but contrary to several similar studies that reported good agreement between farmer and laboratory assessments (Berazneva, McBride, Sheahan, & Guerena, ; Laekemariam, Kibret, & Mamo, ; Yageta, Osbahr, Moromoto, & Clark, ; Yeshaneh, ). The differences in farmer‐identified fertility classes in these studies were largely attributed to soil management rather than inherent properties of the soil.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to Laekemariam et al (2017) and Kome, Enang, and Yerima (2018), there seemed to be a relationship between farmer fertility assessment and farm practices such as crop management, resource allocation and time of planting as well as general cropping systems. Farmers acknowledged the ability of fertile soils to adequately support crop growth and that they require less manure compared to perceived infertile soils.…”
mentioning
confidence: 96%
“…The farmers' perception and soil lab results showed that farmers' local knowledge is vital, and should be valued and combined with scientific findings to have a better soil type and fertility status information. Farmer's described and classified the soils using locally acquired knowledge from generations of experience that fit local conditions [31]. Orimoloye [32] found that farmer's soil fertility ranking was significantly associated with values of organic carbon and available P gained from lab analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Such knowledge transfer across agro-ecological zones may have been responsible for the common farmer perception that red soils are less fertile than black and brown soils. Farmers describe and classify their soils using a holistic approach and use relatively homogeneous soil classification indicators across agro-ecologies (Laekemariam et al, 2017). Accordingly, farmers have been using soil colour, soil texture, soil depth, topography and drainage, as well as crop performance as criteria to categorize their land into fertile and less fertile fields (Belachew & Abera, 2010;Corbeels et al, 2000;Karltun et al, 2013;Yeshaneh, 2015).…”
Section: Farmers' Perception Of Soil Fertility Across Agro-ecological Zones and Farm Typologiesmentioning
confidence: 99%
“…In the low and midlands, a higher variability between fertile and less fertile fields was observed for soil pH and P av . Farmers considered red soils as less fertile and used this as an indicator for soil acidity (soil pH) (Laekemariam et al, 2017). The low P av values might have been a result of P fixation in acidic soils (Agumas et al, 2014).…”
Section: Farmers' Perception Of Soil Fertility Across Agro-ecological Zones and Farm Typologiesmentioning
confidence: 99%